Molecular identification of bacteria present in the soils of the Madhupur Sal and the Sunderban mangrove forests of Bangladesh (Dhaka University Journal of Biological Sciences, 2012)
The present study aimed at identifying the soil bacterial communities in the Madhupur Sal and the Sunderban mangrove forests, the two important forests of Bangladesh. Soil bacteria were identified through sequencing of PCR?amplified fragments of bacterial 16S rDNA. The results showed that the bacterial communities of the Madhupur Sal forest soils and that of the Sunderban mangrove forest soils differed in the morphology of the cells. Data presented here also showed that the bacterial communities of the Sunderban mangrove forest soils were more diverse than that of the Madhupur Sal forest soils as revealed by phylogenetic tree analysis of the 16S rDNA sequences.DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11509Dhaka Univ. J. Biol. Sci. 21(2): 117?123, 2012 (July)